Effects of 12 weeks of circuit training and L-tryptophan supplementation on physical fitness and metabolic syndrome in menopausal women - Hyun-Seok Cho; Tae-Hee Lee; Man-Gyoon Lee (Korea Institute of Sport Science, 2020)
Purpose The study was designed to investigate the effects of 12 weeks of circuit training and L-tryptophan supplementation on physical fitness and metabolic syndrome. Methods Forty-one menopausal women were randomly assigned to one of three groups. i.e., combined circuit training and L-tryptophan supplementation group (CT+T: n=14), L-tryptophan supplementation group (T: n=14), and control group (CON: n=13). The subjects in CT+T exercised three sessions per week and took 3g of L-tryptophan per day for 12 weeks. The subjects in T took 3g of L-tryptophan per day for 12 weeks. The subjects in CON were asked to maintain their life pattern for the same period of intervention. Physical fitness and metabolic syndrome-related variables were measured at pre- and post-test. The data were compared by utilizing a repeated two-way ANOVA. Results Main results of the study were as follows: 1) Standing long jump, one leg standing with eyes closed, sit-and-reach, sit-up, and maximal oxygen uptake increased significantly in CT+T. 2) Body weight, body mass index, waist circumference, waist-hip ratio, fat mass, and percent body fat decreased significantly in CT+T. 3) Total cholesterol decreased significantly in CT+T. 4) Fasting plasma glucose (FPG), fasting plasma insulin, and HOMA-IR decreased significantly in CT+T. FPG and HOMA-IR decreased significantly in T. 5) Systolic blood pressure, diastolic blood pressure (DBP), mean arterial pressure (MAP), and rate pressure product decreased significantly in CT+T. DBP and MAP decreased significantly in T. 6) Number of metabolic syndrome risk factors decreased significantly in CT+T and T. Conclusion It was concluded that the circuit training and L-tryptophan supplementation would have positive effects on physical fitness and metabolic syndrome, and that L-Tryptophan supplementation would have positive effects on metabolic syndrome by improving insulin resistance and hypertension in menopausal women.